ARSITEKTUR NARASI DI PASAR BUKU KWITANG - Alicia Arleeta; Fermanto Lianto (Jurusan Arsitektur dan Perencanaan, 2022)
Kwitang Book Market-Senen is now no longer a book centre for Jakarta. Physical and social degradation as well as reduced economic activity in the Kwitang Book Market began with the regional control carried out by the DKI Regional Government and the lack of action taken by both the government and economic actors to adapt in the digital era. This research aims to re-create the Kwitang Book Market as a Jakarta book centre with the concept of spatial travel. This concept emphasizes the tourist attraction of reading books at the Kwitang Book Market. The spatial journey is processed through the memory of the heyday of Kwitang. The genius loci of the area and the formation of the communal space of books. The method used is the descriptive qualitative method with the help of pictures, maps, and diagrams. In addition, there is also a phenomenological method to explore the Senen area and the Kwitang Book Market. The design method used is narrative architecture which tells the culture of reading books and the sundries of the world of books. The conclusion of this research is to revive the book centre; it is necessary to update social activities and adapt economic actors in the digital era. The solution found in the research is to create a communal space that supports book social activities and the concept of travel with a book reading culture so that the atmosphere that occurs in the area is not artificial and varied. Keywords: Book Market; Community; Kwitang; Narration Abstrak Pasar Buku Kwitang-Senen sekarang sudah tidak lagi menjadi sentra buku Jakarta. Degradasi fisik dan sosial serta berkurangnya kegiatan ekonomi di Pasar Buku Kwitang diawali dengan adanya penertiban kawasan yang dilakukan oleh Pemda DKI dan kurangnya tindakan yang dilakukan baik pemerintah maupun pelaku ekonomi untuk beradaptasi di era zaman digital. Tujuan dari penelitian ini adalah menjadikan kembali Pasar Buku Kwitang sebagai sentra buku Jakarta dengan konsep perjalanan spasial. Konsep ini menekankan pada atraksi wisata membaca buku di Pasar Buku Kwitang. Perjalanan spasial diolah melalui memori masa jaya Kwitang, genius loci kawasan dan pembentukan ruang komunal buku. Metode yang dipergunakan adalah metode deskriptif kualitatif dengan bantuan gambar, peta, dan diagram. Selain itu juga metode fenomenologi untuk menelusuri kawasan Senen dan Pasar Buku Kwitang. Metode perancangan yang digunakan adalah arsitektur narasi yang menceritakan kultur membaca buku dan serba serbi dunia buku. Kesimpulan dari penelitian ini adalah untuk menghidupkan kembali sentra buku, perlu adanya pembaruan kegiatan sosial dan adaptasi pelaku ekonomi di era digital. Solusi yang ditemukan dalam penelitian yaitu membuat ruang komunal yang mengayomi kegiatan sosial buku dan konsep perjalanan dengan kultur membaca buku sehingga suasana yang terjadi di dalam kawasan tidak semu dan bervariasi.